A PESQUISA DA PRÓPRIA PRÁTICA PEDAGÓGICA: UMA AÇÃO POSSÍVEL? - Abreu, Roberta Melo de Andrade (2008)
The aim of this work is to investigate how the teachers of early childhood education understand the act to research the practice of themselves; and to compare the views of the teachers with the specific theoretical frame. To reach these objectives, we use the qualitative approach. The data that serve as basis of this study were obtained from interviews with five teachers of a public school in the city of Salvador - Bahia. We start with the analysis of the historical context of the investigation, its concept, as well as the ones of the teacher-esearcher. in this way, we explore the different definitions of research on teaching, through the ideas of theoreticians who argue the subject. Besides, we examine the categories and subcategories treated during the practical activities of research. Such categories emerge naturally from interviews carried with managers and teachers of the searched institution and from the recurrence in their comments. We present the following main results from the categories constructed in the process of research: the understanding of the interviewed professionals about the research of the practice of themselves is limited and mistaken. We found a universe in which there is no the exercise of research of the practice, because the teachers are entangled in several seroius problematics, as explicited in our registers. We conclude affirming that, despite the researched professionals do not research the practice, we suggest that this is a possible action and that it is also materialize through continuous formation in service.(AU)